2023
DOI: 10.1002/masy.202200024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Conformation and Intermolecular Interactions of Linear and Cyclic Amylose Derivatives in Solution

Abstract: Four kinds of rigid and semiflexible ring polymers are synthesized from flexible cyclic amylose. Their conformational properties in dilute solution are determined from dimensional and hydrodynamic properties in terms of the wormlike ring model. The helix rise per residue h of some ring polymers is larger or smaller than that for the corresponding linear chains, indicating that the local helical structure of the ring polymer is not the same as that for the linear chain. Intermolecular interactions detected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…[15][16][17] On the contrary, we found that cyclic amylose tris(phenylcarbamate) (cATPC) has a negative second virial coefficient in the theta solvent of linear amylose tris(phenylcarbamate) (ATPC), 18 indicating that the intermolecular interactions between the strained helices of the rigid cyclic cATPC chains via solvent molecules are different from those of the linear chain. 19 Highly branched cyclic dextrin (HBCD), which was developed by Takata et al, 20,21 is an amylopectin-based polysaccharide that has a relatively narrow molar mass distribution. We have recently prepared a 3,5-dimethylphenylcarbamate derivative of HBCD (HDMPC) 22 which was only soluble in good solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] On the contrary, we found that cyclic amylose tris(phenylcarbamate) (cATPC) has a negative second virial coefficient in the theta solvent of linear amylose tris(phenylcarbamate) (ATPC), 18 indicating that the intermolecular interactions between the strained helices of the rigid cyclic cATPC chains via solvent molecules are different from those of the linear chain. 19 Highly branched cyclic dextrin (HBCD), which was developed by Takata et al, 20,21 is an amylopectin-based polysaccharide that has a relatively narrow molar mass distribution. We have recently prepared a 3,5-dimethylphenylcarbamate derivative of HBCD (HDMPC) 22 which was only soluble in good solvents.…”
Section: Introductionmentioning
confidence: 99%
“…15–17 On the contrary, we found that cyclic amylose tris(phenylcarbamate) (cATPC) has a negative second virial coefficient in the theta solvent of linear amylose tris(phenylcarbamate) (ATPC), 18 indicating that the intermolecular interactions between the strained helices of the rigid cyclic cATPC chains via solvent molecules are different from those of the linear chain. 19…”
Section: Introductionmentioning
confidence: 99%